Knowledge based view of university tech transfer: A systematic literature review and meta-analysis - Clovia Hamilton; Simon P. Philbin (Administrative Sciences, 2020)
Research and technology commercialization at research-intensive universities has helped to develop provincial economies resulting in university startups, the growth of other new companies and associated employment. University technology transfer offices (TTOs) oversee the process of technology transfer into the commercial marketplace and these organizational units can be considered in the context of enabling effective knowledge management. However, what enables productive TTO performance has not been comprehensively researched. Therefore, this research study adopted the knowledge-based view as the theoretical construct to support a comprehensive investigation into this area. This was achieved through employing a systematic literature review (SLR) combined with a robust meta-analysis. The SLR identified an initial total of 10,126 articles in the first step of the review process, with 44 studies included in the quantitative synthesis, and 29 quantitative empirical studies selected for the meta-analysis. The research study identified that the relationship between TTO knowledge management and knowledge deployment as well as startup business performance is where TTOs secure the strongest returns.
Keywords: 350; knowledge-based view (KBV); patent licensing; systematic literature review (SLR); technology commercialization; technology transfer; university technology transfer